求积分 ∫(1 0)dy∫(1 y)e^(-x^3)dx 提示:把Y型变成X型.我算到∫(1 0)dx∫(x 0)e^(
1个回答
∫(1 0)dy∫(1 y)e^(-x^3)dx
= ∫(1 0)dx∫(x,0)e^(-x^3)dy
你是正确的
相关问题
高等数学改变积分次序∫(0-1)dx∫(x-1)(e^y∫(0-1)dx∫(x-1)(e^y²)dy变换积分顺序,如何算
1.求积分:∫(1.0)x√1-x^2dx 2.设y=y(x)由方程e^y+xy-sinx=0确定,求dy/dx
一道积分题∫[0,1]dx∫[x,1]e^(-y^2)dy
(1+2e^(x/y))dx+2e^(x/y)(1-x/y)dy=0
D={(x,y)|0≤x≤y,0≤y≤1,}.积分∫(上限1限0)x^2dx∫(上1下x)e^(-y²)dy为
计算二重积分:∫[0,1]dx∫[0,x^½]e^(-y²/2)dy
求I=∫(1,0)dx∫(1,x)e^y^2dy
求下列微分方程通解 (1+e^x/y)dx+e^x/y(1-x/y)dy=0
求三次积分∫(0,1)dx∫(0,√1-x²)dy∫(0,√1-x²-y²)√x²